The State of the Global Education Crisis : A Path to Recovery - UNESCO; UNICEF; World Bank (UNESCO, Paris, UNICEF, New York, and World Bank, Washington, DC, 2021)
Even before Coronavirus disease 2019 (COVID-19) hit, the world was already experiencing a learning crisis. 258 million primary- and secondary-school age children and youth were out of school. Many children who were in school were learning very little: 53 percent of all ten-year-old children in low- and middle-income countries were experiencing learning poverty, meaning that they were unable to read and understand a simple age-appropriate text at age 10. This report spotlights how COVID-19 has deepened the education crisis and charts a course for creating more resilient education systems for the future. Section one gives introduction. Section two documents COVID-19’s impacts on learning levels by presenting updated simulations and bringing together the latest documented evidence on learning loss from over 28 countries. Section three explores how the crisis has widened inequality and had greater impacts on already disadvantaged children and youth. Section four reviews evidence on learning recovery from past crises and highlights current policy responses that appear most likely to have succeeded in stemming learning losses, while recognizing that the evidence is still in a nascent stage. The final section discusses how to build on the investments made and the lessons learned during the pandemic to accelerate learning recovery and emerge from the crisis with increased education quality, resilience, and equity in the longer term.